Children's Sports Injuries
In this section we will be looking at problems that are unique to children and the growing years. Most of the unique problems that occur in children occur as a result of properties of their bone, cartilage or growth plates. Children are susceptible to injuries of their growth plates and fractures that occur in ways that can only occur when a growth plate is present. These are called epiphyseal fractures and have a whole system of classification into 5 types. The other type of fracture that occurs in children is called a greenstick fracture. This name comes from the similarity of certain long bone fractures to that of a broken tree branch that is young and green. The outer layer of bone is very thick in children and when a fracture occurs the outer layer may not completely crack itself. The attachments may remain in the same fashion as a green stick would retain some attachments if one attempted to crack it in two.